Musculoskeletal ultrasound images-contrast enhancement - Gupta, R. (IEEE Computer Society, 2014)
Ultrasound has assisted medical practitioners for decades in non-invasive diagnosis of several physical ailments. Ultrasound is continuously promoted by physicians and radiologist because of its features such as use of non-ionizing radiations, non-invasive nature, real time diagnosis, portability, over existing imaging modalities such as Magnetic resonance imaging (MRI) and Computed tomography (CT). Despite many advantages, images obtained from ultrasound equipment suffer from loss of resolution and contrast. In this paper, contrast enhancement of ultrasound image is performed using adaptive statistical method and comparison with original ultrasound image was performed. The quantitative analysis was performed based on three different measurement indices. The measurement indices used to evaluate the performance of contrast enhancement images are universal quality index (UQI), structural similarity index (SSI) and signal to noise ratio (SNR). The ultrasound enhanced and original images are shown for visual references. The quantitative comparison suggests gamma correction to perform best among the chosen methods. The analysis was performed based on real dataset collected from University Malaya Medical Center on patients suffering from MSK disorder in shoulder. Total of 37 images from 23 patients were evaluated to verify the study. Later, several dataset from patients will be collected and qualitative assessment of images will be performed to validate the study for all images. Â© 2014 IEEE.